A Critical Analysis on the Book Journey and Room in Xavier de Maistre’s Work (Le Voyage et la Chambre Dans L'oeuvre de Xavier de Maistre) - Behrouz Avazpour; Nader Shayganfar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the field of criticism of art, Gilbert Durand has invented five methods, and in this case, he has been directly influenced by Iranian Islam. Despite this, we do not know him fundamentally, we have not translated his works into our language, and we have not addressed them as we should. According to experts, one of his works which represents his intellectual system and consequently the substructure of his innovative methods, is a book that, according to him, is in fact an expanded version of a not so voluminous treatise entitled “Journey and Room in Xavier de Maistre’s Work”, the one which its analysis is the main subject of this article: this treatise seeks to explain the new system of thought, conceiving the invention of a new method of critique, mythocritic. In this treatise, based on the system and the method in question, a work by the French novelist de maistre is analyzed. This analysis had three main pillars: literary, psychological, and mythological. There are some criticisms of these pillars which were taken into account in this article. On the contrary, it should not be overlooked that the system in question, analytical mythology, is one of the most applied artistic mythologies, just as the method in question, mythocritic, which is one of the most practical methods of artistic criticism.